Sparkol Videoscribe: Interesting Learning Video Media for Thematic Learning of Kalijaga Permai Elementary School Teachers - Siska Firmasari; Tarmidzi Tarmidzi; Mudopar Mudopar; Nurul Ikhsan Karimah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sparkol Videoscribe is a software for creating exciting learning videos by inserting images and sound, as one of the media uses technology. The lack of teacher knowledge in making technology-based learning media requires solutions, especially online learning modes that require teacher creativity in delivering subject matter. For this reason, the implementation of a workshop in the form of training and mentoring in the use of Sparkol Videoscribe software to make thematic learning videos. The activity results showed that the teachers enthusiastically accepted all the activities so that they could produce various thematic learning videos. The learning videos are made by themselves according to the creativity of the teachers. The quality and quantity of learning videos made from the training and mentoring activities are very encouraging. The teachers' enthusiasm for learning from the results of the post-activity evaluation shows indicators of success and a positive response from the training participants of 97.86%.